ANALISIS YURIDIS TERHADAP TRANSAKSI E-COMMERCE BERDASARKAN HUKUM INTERNASIONAL DAN HUKUM NASIONAL - Esthalita Octavia Tobing; Jelly Leviza; Mahmul Siregar (Journal of USU International Law, 2017)
ABSTRACTThe development of information technology is currently experiencing rapid progress. This development apparently brings impacts on a variety of life sectors including trading world. One form of the uses of much developing, most influential, and most widely used information technology is e-commerce (Electronic Trade). The development in trading world with this e-commerce has to be supported by the development in the law that regulates trade related problems in internet media. This technology and information facility development or commonly called cyberspace also brings quite big impacts on the regulation in national and international laws. The research problems are how the concept of e-commerce transaction is, how e-commerce is regulated in international laws, an how e-commerce is regulated in national laws. This research is entitled “The Juridical Analysis of E-Commerce Transactions according to International and National Laws”. This is a descriptive normative juridical research. The data used in this research are secondary legal materials. They are collected through library study and analyzed qualitatively. The legal problems resulted from e-commerce transactions is the problems in data verification in e-commerce creating obstacles to state policies that impedes e-commerce transactions. E-commerce is regulated in UNCITRAL Model Law on Electronic Commerce which is not enforceable, but it is the reference to be implemented in national law by the countries. UNCITRAL has regulated the validity requirement to bind all parties in an e-commerce transaction. the Law No. 11/ 2008 on Electronic Information and Transaction, the Law No. 82/2012 on the Conduct of Electronic System and Transaction, and the Law No. 8/1999 on UUPK (Consumer’s Protection) as the national laws regulate the provisions of e-commerce transactions and the adequate legal protection for consumers to make e-commerce transactions. Keywords:       E-Commerce, Electronic Transaction, National Law, UNCITRAL